2022
DOI: 10.15366/rimcafd2022.86.006
|View full text |Cite
|
Sign up to set email alerts
|

Motivación Y Barreras Del Desplazamiento Activo en Los Profesores: Un Estudio Exploratorio

Abstract: El presente trabajo tuvo por objetivo conocer la relación entre la motivación intrínseca y motivación extrínseca con las barreras al desplazamiento activo en docentes. Se reclutaron un total de 156 profesores de 25 y 56 años (37.98 ± 12.28). Se utilizó una adaptación del cuestionario BREQ-3 para medir la motivación hacia el desplazamiento activo. Las barreras percibas se midieron con la escala BATACE. Se realizaron análisis descriptivos, correlaciones y modelos de regresiones de las variables de estudio. Los r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…As a consequence, the majority of the sample compri to university. These findings are consistent with previous studie passive means of transport were the most commonly used to c [4, 5,24,33,34]. The main difference in our results comes from the of Balearic Islands is located 7-8 km away from the city and that in previous studies for ACU was 2.6 km by walking and 5.1 km by although more than half of the study participants resided in the c pants live in other towns that are located even further from unive in the study by Molina et al (2015), in which students lived close commuting mode was walking [35].…”
Section: Mode Of Commutingsupporting
confidence: 92%
See 3 more Smart Citations
“…As a consequence, the majority of the sample compri to university. These findings are consistent with previous studie passive means of transport were the most commonly used to c [4, 5,24,33,34]. The main difference in our results comes from the of Balearic Islands is located 7-8 km away from the city and that in previous studies for ACU was 2.6 km by walking and 5.1 km by although more than half of the study participants resided in the c pants live in other towns that are located even further from unive in the study by Molina et al (2015), in which students lived close commuting mode was walking [35].…”
Section: Mode Of Commutingsupporting
confidence: 92%
“…As a consequence, the majority of the sample comprised passive commuters to university. These findings are consistent with previous studies, which indicated that passive means of transport were the most commonly used to commute to university [4, 5,24,33,34]. The main difference in our results comes from the fact that the University of Balearic Islands is located 7-8 km away from the city and that the threshold indicated in previous studies for ACU was 2.6 km by walking and 5.1 km by cycling [5].…”
Section: Mode Of Commutingsupporting
confidence: 92%
See 2 more Smart Citations